The Art of Transitioning Pediatric Patients with Rheumatic Diseases to Adult Rheumatologists - Florence Kanakoudi-Tsakalidou (Mediterranean Journal of Rheumatology, 2016)
The process of transitioning adolescents or young adults with rheumatic diseases from pediatric to adult Rheumatology clinics is an art. Its success requires bilateral special handling and coordinated cooperation. According to Greek legislation, transition is implied at the challenging age of 18 years, i.e., at the borderline of adolescence and adulthood. Therefore, the physician has to adopt a specific attitude towards the patient in order to achieve patient compliance to his guidelines and treatment participation. The process begins with the periodic updating of the patient/family on the disease progress and, in case of immunosuppressive therapy, on documented information regarding potential treatment consequences: this policy aims to motivate the adolescent to take responsibility and participate consciously in decision-making. Thereafter, the patient/family will be educated on the need for future periodic assessments by an adult Rheumatologist, who has the skills and experience to manage adult patient problems. The pediatric Rheumatologist identifies and records the patient/family capability to respond to the circumstances and overcome probable obstacles. Additionally, he or she estimates the potentials of the future patient care center/clinic. By co-estimating all these factors, a personalized “transition policy” is scheduled. Various models of transition have been proposed over time. Independently of the model applied, the critical factors for a successful transition are the patient’s readiness for self-management and psychosocial maturity as well as the family’s acceptance to let the young adult cope with his/her own life.